Investigation of Hammada scoparia antidiabetic activity and toxicity in rat - Meriem Zerriouh,; Salima Merghache,; Rabah Djaziri,; Chaouki Selles,; Fatima Zohra Sekkal, (International Journal of Phytomedicine, 2014)
Objective To investigate Hammada scoparia claimed antidiabetic effect, and to search for potential nontoxic active principles. Methods Aqueous and methanol extracts were prepared from H. scoparia areal parts, and their phytochemical constitution was defined. Then they were subjected to three procedures to check their antidiabetic effect. The first (acute effect on fasting glycemia) and the second (oral glucose tolerance test, OGTT) were carried out in normal rats, while the third procedure (7 days treatment) was carried out in streptozotocin-diabetic rats. Methanol extract was also subjected to further studies; sub-chronic oral toxicity test (21days), effect on postprandial glycemia in normal rats and effect on intra-tissue glycogen concentrations. Finally methanol extract was fractionated on chromatography column; each fraction was thoroughly analysis using phytochemical tests and subjected to OGTT in normal rats. Results Using the three procedures, only the methanol extract (containing flavonoids, alkaloids and saponins) showed an antidiabetic effect similar to glibenclamide effect, and this was only when hyperglycemia was induced by oral glucose charge. On the other hand methanol extract had no toxicity in rats; it had no effect on postprandial glycemia or on intra-tissue glycogen concentrations. Four fractions were obtained using chromatography column, FA (containing flavonoids), FB (alkaloids, saponins), FC (alkaloids), and FD (saponins). Unlike the antihyperglycemic effect observed with methanol extract in normal rats, none of these fractions were effective. Conclusion Hammada scoparia could be a promising source of new antidiabetic agents, further studies are necessary to find its active principles and to understand its mechanism of action.